(3MGTjI bhd CMeOjIs - (3GdYeQj GdMfaj, CHh GdYHGS, GHf GdNVQ, bhd CMeO (B- (3TgGH GdOjf, CMeO Hf eMeO Hf YeQ Hf eSde, (B785 (3g`s ((3eUWai Hf Ydj GdMUchjs)
(3ChdgG (B:s
(3MeOG dc Ydi eG efMJ Hg ef eYGQa GdCaGVd adeG cGfJ GdahGFO GdafGQjI Ydi eG dG Yf GdZehV hGdEZdGb heY gPG ENhGf GdReGf QGZHhf ajgG ZGjI QZHI hGTJjGb YdbJ YdjgG eG jcTa GdZdGb hjRj GdZehV MJi jJjSQ dge s
(3BNQgG (B:s
(3eYJeOG Ydjg HdG Tc aj GdOYhI Edi SHjd GdMb dcf HGdfSHI Edi faS GdeSJOd GdYeOI gh GdHQgGf abW HdG Tc dGfg jajO Gdjbjf HdG QjH HNdGa GdBNQjjf hdgPG bUQ GdeUfa GdYeOjI aj GdHQgGf JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1/225s
(3GdCYdGe (B1/225s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs